2015
DOI: 10.1371/journal.pone.0127086
|View full text |Cite
|
Sign up to set email alerts
|

Redox Proteomics of the Inflammatory Secretome Identifies a Common Set of Redoxins and Other Glutathionylated Proteins Released in Inflammation, Influenza Virus Infection and Oxidative Stress

Abstract: Protein cysteines can form transient disulfides with glutathione (GSH), resulting in the production of glutathionylated proteins, and this process is regarded as a mechanism by which the redox state of the cell can regulate protein function. Most studies on redox regulation of immunity have focused on intracellular proteins. In this study we have used redox proteomics to identify those proteins released in glutathionylated form by macrophages stimulated with lipopolysaccharide (LPS) after pre-loading the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 71 publications
2
67
0
Order By: Relevance
“…Park et al (25,26), who generated adducts by overnight incubation of reduced Prxs with 10 mM GSSG, focused mainly on glutathionylation of Cys-83 in Prx1 (which is not present in Prx2) and reversal by sulfiredoxin. Others have detected glutathionylated Prxs in proteomic screens and observed secretion from cells under oxidative and inflammatory stress (27,28). Reduction of Prx3 by Grx2 has also been observed, but in this case, the disulfide was reduced directly without involving a glutathionylated intermediate (6).…”
Section: Table 4 Detection Of Glutathionylated Prx2 In Erythrocytes Fmentioning
confidence: 96%
See 1 more Smart Citation
“…Park et al (25,26), who generated adducts by overnight incubation of reduced Prxs with 10 mM GSSG, focused mainly on glutathionylation of Cys-83 in Prx1 (which is not present in Prx2) and reversal by sulfiredoxin. Others have detected glutathionylated Prxs in proteomic screens and observed secretion from cells under oxidative and inflammatory stress (27,28). Reduction of Prx3 by Grx2 has also been observed, but in this case, the disulfide was reduced directly without involving a glutathionylated intermediate (6).…”
Section: Table 4 Detection Of Glutathionylated Prx2 In Erythrocytes Fmentioning
confidence: 96%
“…Glutathionylation of the isolated proteins has been observed but only after extended incubation with nonphysiological GSSG concentrations (25,26), and recycling of Prx1 and Prx2 by GSH and Grx1 was not apparent in initial studies (21). However, glutathione adducts have been detected in cell systems (25,27,28) and could therefore be physiologically relevant. We have characterized the interactions between GSH and Prx2 using mass spectrometry to detect products.…”
mentioning
confidence: 99%
“…Therefore, it is imperative that each protein is validated. In our studies, we normally provide the list of the identified proteins as supplementary data but report only those validated in the main body of the manuscript (23). This makes it possible for others to eventually validate other proteins of interest.…”
Section: Studies Specifically Addressing the Proteomic Identificationmentioning
confidence: 99%
“…Typically, a Western blot is required to measure the protein in the supernatant of LPS-stimulated versus unstimulated cells. This should be done with a proper number of replicates and, possibly, followed by densitometry and statistical analysis (23). Of course, if an enzyme-linked immunosorbent assay (ELISA) or any other assay (such as an enzymatic assay in case the protein is an enzyme) are available, that would be preferable as it may be more quantitative than a Western blot.…”
Section: Studies Specifically Addressing the Proteomic Identificationmentioning
confidence: 99%
See 1 more Smart Citation